2006
DOI: 10.1002/tox.20153
|View full text |Cite
|
Sign up to set email alerts
|

Determination of toxic carbonyl compounds in cigarette smoke

Abstract: Toxic carbonyl compounds, including formaldehyde, malonaldehyde, and glyoxal, formed in mainstream cigarette smoke were quantified by derivatization-solid phase extraction-gas chromatography methods. Cigarette smoke from 14 commercial brands and one reference (2R1F) was drawn into a separatory funnel containing aqueous phosphate-buffered saline. Reactive carbonyl compounds trapped in the buffer solution were derivatized into stable nitrogen containing compounds (pyrazoles for -dicarbonyl and , -unsaturated ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 35 publications
2
144
1
Order By: Relevance
“…72,73 Cigarette smoke is implicated in these aggregates in humans with chronic obstructive pulmonary disease. 72 Because our study demonstrates that diacetyl alters proteostasis and cigarette smoke contains diacetyl, 74,75 the results suggest that diacetyl may play a role in chronic obstructive pulmonary disease in addition to its role in flavorings-related lung disease. 11,12 In addition, during autophagy, SQSTM1 is phosphorylated, a process that activates the Kelch-like ECHassociated protein 1 (Keap1)enuclear factor E2erelated factor 2 (Nrf2) pathway.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 82%
“…72,73 Cigarette smoke is implicated in these aggregates in humans with chronic obstructive pulmonary disease. 72 Because our study demonstrates that diacetyl alters proteostasis and cigarette smoke contains diacetyl, 74,75 the results suggest that diacetyl may play a role in chronic obstructive pulmonary disease in addition to its role in flavorings-related lung disease. 11,12 In addition, during autophagy, SQSTM1 is phosphorylated, a process that activates the Kelch-like ECHassociated protein 1 (Keap1)enuclear factor E2erelated factor 2 (Nrf2) pathway.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 82%
“…This treatment induced 50 to 90% of cytotoxicity in NHBE and NHLF, respectively. It should be noted that 50 M Acr is equivalent to Acr concentration in lung tissue in an individual who has smoked 10 -20 cigarettes (20). The Acr cytotoxicity was determined by WST-1 method as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…By mapping Acr-dG adduct distribution at the nucleotide level in Acr-treated normal human bronchial epithelia (NHBE), we have found that the Acr-DNA binding spectrum in the p53 gene coincides with p53 mutational spectrum in lung cancer (19). Because Acr is abundant in tobacco smoke and its level is up to 10,000-fold that of benzo-(a)pyrene (20,21), we concluded that Acr is a major lung carcinogen. This conclusion is consistent with the finding that lung cancer is the number one cancer death in Taiwanese women, and yet only 5% of these women are tobacco smokers and that lung cancer incidence was greatly reduced in Taiwanese women in households that were equipped with fume extractors (22)(23)(24)(25)(26).…”
mentioning
confidence: 93%
“…Acr is one of the most abundant compounds generated in CS; the amount of Acr in a single cigarette, depending on the manufacturer, ranges from 10 to 500 g (8,31). The total amount of PAHs present in CS, in contrast, is in the range of just a few micrograms (8).…”
Section: Acr-dg Adducts Induce G-to-t Transversion Mutations In Humanmentioning
confidence: 99%